Kajian Kritik Seni Instalasi Tisna Sanjaya - "32 Tahun Berpikir dengan Dengkul" - Dea Aulia Widyaevan (JURNAL RUPA, 2017)
Art critics has become a way to reveal and appreciate content lies behind its appearences. Thus signified an important role on reading an art work by analyze the reasoning behind the artworks, through the artist statement, intention and the translation on relating medium. The process of reasoning require several steps which enhance the art critic's methods. On this case , a method of Feldman' art critics has been applied to anaylize an installation work of Tisna Sanjaya - "32 Tahun Berpikir dengan Dengkul". Feldman theory divide art critics method into four steps: description, formal analysis, interpretation and evaluation. This analysis require contextual reading due the impact of this art works into social, politic relation outside the artworld itself. Tisna's work has become one pioneer on installation artwork in Bandung, which also has a significance role of enggaging public reaction which create a paradoxes. Further more, provoke the government security (Satpol PP) to burn this artwork in Babakan Siliwangi as well as his other works "Doa untuk yang Matiâ€.